Mitigation of low frequency oscillations in power systems based on Mamdani fuzzy inference. (August 2019) - Gao, Hong-Liang; Zhan, Xi-Sheng; Yuan, Yi-Ran; Pan, Zi-Jie; Yuan, Guo-Long
Several methods have been proposed and implemented to improve the power system stability. Based on the theory of proportional-integral-derivative (PID) excitation control and the composition principle of fuzzy PID controller, a novel PID controller based on Mamdani fuzzy inference (MFPID) is proposed in this paper. The proposed controller realizes the self-adjustment of the excitation controller parameter. Furthermore, the MFPID and power system stabilizer (PSS) subsection switch control strategy (MFPID-PSS) is presented based on the advantages of PSS and MFPID. In MFPID-PSS strategy, by switching the control strategy between MFPID and PSS at appropriate moment, the MFPID-PSS method acquires the overshoot as small as PSS, and at the same time acquires the adjusting time as short as MFPID. The simulation results demonstrate that the MFPID-PSS method improves the power system stability and has better mitigation effect for low frequency oscillations in power systems after disturbances.